HUKUM PRAKTIK GADAI TANAH SAWAH DALAM PERSPEKTIF FIQIH MUAMALAH - Peby Ziana Sirojul Munir; Asep Salahudin (Mutawasith: Jurnal Hukum Islam, 2018)
The practice of pawn has existed since the era of Rasullullah Saw. And even practicedby the prophet, and likewise until now, the practice of mortgage is still done by society. Thestudy of the practice of pawnshop has been widely discussed by scholars, including the fourpriests of the sect. The view of the scholars about the ability to do the same pledge but stillthere are some differences in terms of the use of mortgage goods by the recipient of Pawn(murtahin). This research aims to know the Fiqh law to the practice of soil pledge that iscarried out by the community Hamlet Sindangrasa Sindangbarang Village, whether inaccordance with the provisions that are sharia or not. Because as already mentioned abovethat there are still differences in the opinion of the scholars about the utilization of pawngoods. The methods used in the writing of this thesis are qualitative research methods. Thisresearch is based on the utilization of pawn goods in this case the rice fields are takenadvantage by the creditor.